PKP-PK Unit Personnel Strategy Analysis in Mitigating Aircraft Accidents at Adi Soemarmo Boyolali International Airport - Dwi Permadi; Amelia Puspa Tamara (CV. Rayyan Dwi Bharata, 2023)
This study aims to find out how well and how hard the Aviation Accident Assistance and Fire Fighting (PKP-PK) personnel handle fires at Adi Soemarmo Boyolali International Airport. This research will help by facilitating PKP-PK to follow the safety SOP (Standard Operation Procedure) if an incident occurs. Case study method descriptive qualitative research was used for this study. The PKP-PK unit at Adi Soemarmo Boyolali International Airport was used as a research location. The results of the review show how the progress and progress of the Avionics Accident Management and Fire Fighting (PKP-PK) workforce in tackling fire incidents at the Adi Soemarmo Boyolali World Air Terminal. PKP-PK personnel always carry out their responsibilities in accordance with applicable regulations.